Infrastructure planning, engineering and economics - Goodman, Alvin S.; Hastak, Makarand (McGraw-Hill Education LLC., 2015)
The new edition of this infrastructure planning and management resource has been fully updated and streamlined to improve ease of use for instructors, students, and professionals alike. It features global case studies and includes a new chapter on sustainability for design, construction, and maintenance.